Peran Transformasi Digital dalam Optimalisasi Ekonomi Manajerial di Era Revolusi Industri 5.0. - Devina Karunia; Rahma Eka Rianti; Maharani putri Darussalam; Pupung Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2025)
The era of Industrial Revolution 5.0 emphasizes the importance of collaboration between humans and modern technology in managing economic systems, including managerial aspects. Digitalization serves as a key driver in enhancing efficiency, innovation, and corporate competitiveness. This study aims to assess how digitalization contributes to the optimization of managerial economics in the present era. A qualitative approach was employed, utilizing literature reviews and interviews as methods of data collection. The findings indicate that the implementation of technologies such as artificial intelligence, big data, and digital information systems can accelerate decision-making processes, improve operational efficiency, and foster innovation in products and services. However, challenges remain, including inadequate infrastructure, low digital literacy among the workforce, and resistance to change, which continue to be major obstacles. Therefore, a comprehensive and collaborative strategy involving all relevant stakeholders is essential to ensure the successful integration of digitalization within the context of managerial economics.